Informal child care and adolescent psychological well-being: Hong Kong's "Children of 1997" birth cohort. - Cherry Y Leung (PLoS ONE, 2015)
Informal child care (child care by untrained family members, relatives or employees in the home) in Western populations is often associated with poorer psychological well-being, which may be confounded by socioeconomic position. We examined the association of informal child care, common in non-Western settings, with adolescent psychological well-being, using Hong Kong's Chinese "Children of 1997" birth cohort.Multivariable linear regression was used to examine the adjusted associations of informal child care (at 0.5, 3, 5 and 11 years) with parent-reported Rutter score for child behavior at 11 years, self-reported Culture-Free Self-Esteem Inventories score at 11 years and self-reported Patient Health Questionnaire-9 depressive symptom score at 13 years. Model comparisons were used to identify the best representation of child care, in terms of a critical period of exposure to informal child care (independent variable) at a specific age, combination of exposures to informal child care at several ages or an accumulation of exposures to informal child care.Child care was not associated with behavioral problems. A model considering child care at 3 years best represented the association of child care with self-esteem while a model considering child care at 5 years best represented the association of child care with depressive symptoms. Informal child care at 3 years was associated with lower self-esteem (-0.70, 95% confidence interval (CI) -1.26 to -0.14). Informal child care at 5 years was associated with more depressive symptoms (0.45, 95% CI 0.17 to 0.73).In a developed non-Western setting, informal child care was associated with lower self-esteem and more depressive symptoms.